Belt and Road : The First Decade. - Rogelja, Igor.; Tsimonis, Konstantinos (Newcastle Upon Tyne : Agenda Publishing, 2022)
China's Belt and Road Initiative (BRI) is one of the most talked about and little understood policy initiatives of China. This short book offers a comprehensive, balanced and policy-oriented analysis of the BRI and what it means for western businesses and polities.
5 Is it corrupt by design? -- State capitalism and corruption -- From cadres to capitalists -- A Belt and Road of corruption? -- The Angola Model -- What terms, what standards? -- Cleaning up -- The challenge of BRI 2.0 -- 6 Is it socially responsible? -- Human rights and the BRI -- The "Sinification" of industrial relations? -- The long road towards responsible development -- Conclusion: is there a future for the BRI? -- Globalizing the state sector -- The resilience of the BRI -- References -- Index
Description based upon print version of record.
JSTOR
Keywords: Yi dai yi lu (Initiative : China); Nouvelles routes de la soie; Yi dai yi lu (Initiative : China); China -- Economic policy -- 2000-; Chine -- Politique économique -- 2000-; Economic policy; China; Since 2000